In Sickness and in Health: Job Displacement and Health Spillovers in Couples - Christina Gathmann; Kristiina Huttunen; Laura Jernström; Lauri Sääksvuori; Robin Stitzing (Institute of Labor Economics (IZA), 2020)
We study how a negative labor market shock like job loss generates health spillovers in couples. Using administrative data of all workers and firms matched to mortality and patient records, we document that male job displacement increases the mortality risk for both the man and his partner. For every 10,000 displaced men, there are 27 additional deaths over a 5-year period rising to 115 additional deaths over two decades. Of those, 60% accrue to the displaced worker but 40% are due to excess spousal mortality. Deaths from cardiovascular diseases jump up and hospitalization records show more treatments for alcohol-related disorders and mental health issues. We also find a stunning gender asymmetry: while male job displacement generates large and persistent health effects, no such dire health consequences are observed after a woman loses her job. We explore three explanations for the observed health spillovers: risk sharing through spousal labor supply; earnings losses and the role of public insurance; and the influence of gender roles and family structure.
Keywords: I14; J21; J63; J12; D13; 330; job displacement; mortality; spillovers; added worker; public insurance; gender roles